2021
DOI: 10.3390/v13091850
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Inhibition of HIV Using CRISPR/Cas13d Nuclease System

Abstract: Recently discovered Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR)/Cas13 proteins are programmable RNA-guided ribonucleases that target single-stranded RNA (ssRNA). CRISPR/Cas13-mediated RNA targeting has emerged as a powerful tool for detecting and eliminating RNA viruses. Here, we demonstrate the effectiveness of CRISPR/Cas13d to inhibit HIV-1 replication. We designed guide RNAs (gRNAs) targeting highly conserved regions of HIV-1. RfxCas13d (CasRx) in combination with HIV-specific gRNAs e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 77 publications
0
13
0
Order By: Relevance
“…Further, they reported that RfxCas13d (CasRx) significantly and efficiently inhibited the HIV-1 replication when targeting four separate, non-overlapping sites in the HIV-1 transcript in all the cell line models as well in primary CD4 + T-cells. Therefore their study concluded that the use of the CRISPR/Cas13d nuclease system to target acute and latent HIV infection will endow with an unconventional treatment modality against HIV ( Nguyen et al, 2021 ).…”
Section: Various Applications Of Cas13d In Basic Research and Biomedi...mentioning
confidence: 99%
“…Further, they reported that RfxCas13d (CasRx) significantly and efficiently inhibited the HIV-1 replication when targeting four separate, non-overlapping sites in the HIV-1 transcript in all the cell line models as well in primary CD4 + T-cells. Therefore their study concluded that the use of the CRISPR/Cas13d nuclease system to target acute and latent HIV infection will endow with an unconventional treatment modality against HIV ( Nguyen et al, 2021 ).…”
Section: Various Applications Of Cas13d In Basic Research and Biomedi...mentioning
confidence: 99%
“…While Cas9 produces blunt double-strand cuts, Cas12a produces staggered cuts in dsDNA. Additionally, the Cas13 nuclease which targets the RNA has been used in HIV-1 infected cells with significant results [ 31 ]. With the discovery of multiple nuclease variants, a varied usage of these Cas proteins can be employed in gene editing systems for getting effective results.…”
Section: Crispr/cas System In Genome Editingmentioning
confidence: 99%
“…The RNA-editing Cas13 system has been recently tested against HIV-1 infected cells. The Cas13d system was able to effectively inhibit HIV-1 infection in primary CD4 + T cells and also, suppressed reactivated HIV-1 from latently infected cells [ 31 ]. The CRISPR-Cas13a targets HIV-1 RNA leading to a reduction in viral gene expression.…”
Section: Crispr/cas Mediated Inhibition Of Hiv-1mentioning
confidence: 99%
“…Because Cas12a and, especially, its orthologs Cas12j and Cas12f are much smaller than Cas9, their improved delivery with size-restricted vehicles, such as AAV, viral, and nonviral particles ( Briolay et al., 2021 ), is highly probable and should motivate their development and application in the future. As alternatives to the genetic and epigenetic silencing of HIV, two recent reports demonstrated the efficient suppression of HIV replication and reactivation at the mRNA/gRNA level with Cas13a ( Yin et al., 2020 ) and Cas13d ( Nguyen et al., 2021 ). Interestingly, Cas13a degraded gRNA packed into viral particles.…”
Section: Perspectives In Crispr/cas Anti-hiv Therapy and Concluding R...mentioning
confidence: 99%